2018
DOI: 10.1371/journal.pone.0193001
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative thematic analysis of the phenomenology of near-death experiences

Abstract: Near-death experiences (NDEs) refer to profound psychological events that can have an important impact on the experiencers’ (NDErs) lives. Previous studies have shown that NDEs memories are phenomenologically rich. In the present study, we therefore aimed to extract the common themes (referred to as “features” in the NDE literature) reported by NDErs by analyzing all the concepts stored in the narratives of their experiences. A qualitative thematic analysis has been carried out on 34 cardiac arrest survivors’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 32 publications
8
72
5
Order By: Relevance
“…We found a prevalence of 10% using the same criteria in our previous crowdsourcing online survey on NDE and REM intrusion (Kondziella, Dreier & Olsen, 2019), indicating that this prevalence is quite robust. Unlike most previous reports in which NDE were almost always associated with peace and well-being (Thonnard et al, 2013; Charland-Verville et al, 2015; Martial et al, 2017, 2018; Cassol et al, 2018), we confirmed our earlier findings that many people find their NDE unpleasant (Kondziella, Dreier & Olsen, 2019). However, experiences with the cut-off score of ≥7 GNDES points were reported significantly more often as pleasant (49%) than experiences with a lower score (13%).…”
Section: Discussionsupporting
confidence: 89%
“…We found a prevalence of 10% using the same criteria in our previous crowdsourcing online survey on NDE and REM intrusion (Kondziella, Dreier & Olsen, 2019), indicating that this prevalence is quite robust. Unlike most previous reports in which NDE were almost always associated with peace and well-being (Thonnard et al, 2013; Charland-Verville et al, 2015; Martial et al, 2017, 2018; Cassol et al, 2018), we confirmed our earlier findings that many people find their NDE unpleasant (Kondziella, Dreier & Olsen, 2019). However, experiences with the cut-off score of ≥7 GNDES points were reported significantly more often as pleasant (49%) than experiences with a lower score (13%).…”
Section: Discussionsupporting
confidence: 89%
“…Interviews were transcribed verbatim from these recordings. In a stepwise manner and using an inductive approach, thematic analysis was used to identify themes as well as similarities and differences between participant experiences . One investigator (A.K.)…”
Section: Methodsmentioning
confidence: 99%
“…grouped these codes into categories according to their similarities, organized these categories into themes, and identified quotations that corresponded to the themes. In the final step, all authors evaluated these findings and agreed upon the most salient themes to be highlighted for the article . The current study was approved by the institutional review board at MSKCC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Reports of near-death experiences include, but are not limited to, increased speed of thoughts, distortion of time perception, out-of-body experiences, and visual and auditive hallucinations. 1–3…”
Section: Introductionmentioning
confidence: 99%